2017
DOI: 10.1111/den.12804
|View full text |Cite
|
Sign up to set email alerts
|

Examination time as a quality indicator of screening upper gastrointestinal endoscopy for asymptomatic examinees

Abstract: Endoscopists who do not allot adequate examination time may overlook neoplastic lesions in the upper gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 19 publications
2
54
1
Order By: Relevance
“…Previous studies have shown that slow-speed endoscopists had a higher detection rate for UGI neoplasms than fas- speed endoscopists 23 24 25 . In this study, the neoplasm detection rates showed no significant difference among the fast, moderate, and slow groups.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that slow-speed endoscopists had a higher detection rate for UGI neoplasms than fas- speed endoscopists 23 24 25 . In this study, the neoplasm detection rates showed no significant difference among the fast, moderate, and slow groups.…”
Section: Discussionmentioning
confidence: 93%
“…A few previous studies found an association between inspection time during EGD and detection rates for UGI neoplasms. Results of those studies have shown that slower endoscopists detected a higher proportion of UGI neoplasms than faster endoscopists, suggesting that inspection time may be a useful quality indicator in EGD 23 24 25 . Conversely, other previous studies found that endoscopists require sufficient training and experience to detect gastric cancer properly 12 13 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In a single-centre retrospective trial in Singapore, endoscopists who spent a mean OGD time of longer than 7 min were twice as likely to detect high-risk lesions (OR 2.50, 95% CI 1.52 to 4.12) and three times as likely to detect neoplastic lesions (OR 3.42, 95% CI 1.25 to 10.38) than their counterparts who conducted shorter examinations 62. A similar Japanese study indicated that moderate (5–7 min) and slow (>7 min) endoscopists for OGD identified about twice as many neoplastic lesions (OR 1.90, 95% CI 1.06 to 3.40, and 1.89, 95% CI 0.98 to 3.64, respectively) than quicker (<5 min) endoscopists 63. Park et al retrospectively analysed the data of 111 962 patients who underwent OGD in a health-screening programme and found that slow endoscopists were more likely to detect gastric adenoma or carcinoma 64…”
Section: Consensus Statementsmentioning
confidence: 89%
“…reported that, in 837 cases of endoscopic examination, endoscopists who took a mean <7 min from endoscope insertion to removal did not detect early gastric cancer, whereas those who took a mean of 7 min or more detected four (0.9%) lesions of early gastric cancer. Kawamura et al 2 . analyzed 15,763 endoscopic examinations and found that the detection rate of early gastric cancer tended to be lower among endoscopists who took a mean duration of examination (from endoscope insertion to removal) of <5 min (0.2%) than among those who took a mean duration of 5 min or more (0.4%).…”
Section: Statement 2‐4mentioning
confidence: 99%